Investigation of Wear Behavior of Aluminum Alloy Reinforced with Carbon Nanotubes - Uzunsoy, Deniz; Peng, Tao; Chang, Isaac; Istif, Ilyas (SAE INT, 2014)
The material demands for advanced technologies have led to development of new generation, light-weight, and multifunctional materials. Aluminum matrix composites (AMCs) have captured considerable attention in aviation, space and automotive industries in recent years. Carbon nanotubes (CNT) are one of the most promising candidate of reinforcements used to improve mechanical strength and hardness of metal matrix composites (MMCs). In this study, dry sliding wear behavior of aluminum (Al) matrix (MMCs) reinforced with different amounts (0, 0.5, 1 and 2 wt%) of CNTs were prepared through ball milling, the process was followed by compaction at room temperature and pressureless sintering at 630 degrees C under argon atmosphere for 1hr. Wear tests were performed on a pin-on-disk tribometer against SAE 1040 steel counter body under constant load and sliding speed at room temperature. Worn surfaces of composites were characterized by scanning electron microscopy (SEM) technique in order to identify dominant wear mechanism of the as-produced composite materials. Preliminary result of this study showed that the composite displayed lower wear rate and friction coefficient under mild wear conditions comparing to aluminum alloy without reinforcement.
Keywords: Transportation